Sub-epithelial connective tissue graft for root coverage in nonsmokers and smokers: A pilot comparative clinical study - Chini Doraswamy Dwarakanath; Bheemavarapu Divya; Gottumukkala Naga Venkata Satya Sruthima; Gautami Subadra Penmetsa (Wolters Kluwer Medknow Publications, 2016)
Background: Gingival recession is a common condition and is more prevalent in smokers. It is widely believed that root coverage procedures in smokers result in less desirable outcome compared to nonsmokers', and there are few controlled studies in literature to support this finding. Therefore, the purpose of this study was to evaluate and compare the outcome of root coverage with sub-epithelial connective tissue graft (SCTG) in nonsmokers and smokers. Materials and Methods: A sample of twenty subjects, 10 nonsmokers and 10 smokers were selected each with at least 1 Miller's Class I or II recession on a single rooted tooth. Clinical measurements of probing depth, clinical attachment level (CAL), gingival recession total surface area (GRTSA), depth of recession (RD), width of recession (RW), and width of keratinized tissue were determined at baseline, 3, and 6 months after surgery. Results: The treatment of gingival recession with SCTG and coronally advanced flap showed a decrease in the GRTSA, RD, RW, and an increase in CAL and width of keratinized gingiva in both the groups. However, the intergroup comparison of the clinical parameters showed no statistical significance. About 6 out of 10 nonsmokers (60%) and 3 smokers (30%) showed complete root coverage. The mean percentage of root coverage of 71.2% in nonsmokers and 38% in smokers was observed. Conclusion: The results of the present study suggest that smoking may negatively influence gingival recession reduction and CAL gain. In addition, smokers may exhibit fewer chances of complete root coverage. Overall, nonsmokers showed better improvements in all the parameters compared to smokers at the end of 6 months.